Estrogen receptor β controls MMP-19 expression in mouse ovaries during ovulation. Issue 3 (March 2016) - Nalvarte, Ivan; Töhönen, Virpi; Lindeberg, Maria; Varshney, Mukesh; Gustafsson, Jan-Åke; Inzunza, José
Abstract : Estrogen receptor beta (ERβ/ESR2) has a central role in mouse ovaries, as ERβ knockout (BERKO) mice are subfertile due to an increase in fibrosis around the maturing follicle and a decrease in blood supply. This has a consequence that these follicles rarely rupture to release the mature oocyte. Matrix metalloproteinases (MMPs) are modulators of the extracellular matrix, and the expression of one specific MMP, MMP-19, is normally increased in granulosa cells during their maturation until ovulation. In this study, we demonstrate that MMP-19 levels are downregulated in BERKO mouse ovaries. Using human MCF-7 cells that overexpress ERβ, we could identify MMP-19 to be a transcriptional target of ligand-bound activated ERβ acting on a specificity protein-1 binding site. These data provide a molecular explanation for the observed follicle rupture defect that contributes to the subfertility of female BERKO mice.